Novel Methodologies for Multiaxial Strain Measurements with Piezoresistive Films based on Graphene Nanoplatelets. Issue 12 (24th October 2021) - Yokaribas, Volkan; Kraemer, Peter; Mende, Alexander B.; Ruhkopf, Jasper; Lemme, Max C.; Fritzen, Claus-Peter
Abstract : Many recent investigations in the context of graphene nanoplatelets (GNPs) coatings report surface strain measurements by using piezoresistive sensing capabilities. An often underestimated problem is that the strain field is unknown and the principal strain components as well as their orientations must be determined. Herein, GNP films subjected to multiaxial strain are examined. Experimental results show that although the sensitivity to longitudinal strain is the highest, the ratio between transverse and longitudinal sensitivity exceeds 0.5. The sensitivity to shear strain is much lower. A model assisted study of a random network provides additional guidelines for the different electromechanical sensitivities. In practice, the GNP film is usually subjected to different strains simultaneously so that the multiaxial strain measurement becomes difficult. Therefore, two novel approaches for sensing plane strain components with circular GNP films are developed and successfully verified in experiments. The numerical approach is called strain‐differential electrical impedance tomography (SD‐EIT), where the proposed piezoresistive model elementwise in a finite element model is implemented and the strain components of a strain rosette are reconstructed. Moreover, an analytical approach is derived from SD‐EIT and exhibits further the opportunity to detect anomalies within the piezoresistive sensing behavior of GNP films. Abstract : Graphene nanoplatelets (GNPs) films promote the formation of conductive paths with piezoresistive sensing capabilities. Herein, how the resistance of GNP film is affected by multiaxial strain is theoretically and experimentally examined. To accurately characterize the strain field with GNP films, novel methodologies are presented. The goal is to determine the principal strains in an unknown 2D strain field.